PENGARUH DISIPLIN DAN MOTIVASI TERHADAP SEMANGAT KERJA PEGAWAI PADA DINAS KOMUNIKASI DAN INFORMATIKA KOTA SIBOLGA (Lembaga Pengembangan Kinerja Dosen, 2022)
This study aims to determine whether there is an influence of discipline and motivation on employee morale at the Communication and Informatics Office of Sibolga City. The type of research used in this research is a quantitative research method with a descriptive approach. The sample in this study were employees at the Communication and Informatics Office of the City of Sibolga, with a total of 56 respondents distributing questionnaires. Based on the analysis of the coefficient of determination obtained by 0.603 or 60.3%. This means that what occurs in the dependent variable variation is 60.3% morale determined by the independent variables of discipline and motivation simultaneously and the remaining 39.7% is determined by other factors not discussed in this study. From the results of the T-test in the study, it is known that the T-value for discipline is 3.556, and motivation is 3.418> T-table 2.00575, so the hypothesis states that discipline and motivation partially or individually influence employee morale in communication and informatics in the city of Sibolga is acceptable. Meanwhile, from the results of the F test, it is known that the calculated F value is 40,178 > F table 3.17 and a significance of 0.000 <0.05 so that the hypothesis stating that discipline and motivation have a joint or simultaneous significant effect on employee morale in communication and informatics in the city of Sibolga is acceptable.